Antioxidant and antiapoptotic effects of a Turraea fischeri leaf extract on cryopreserved goat sperm - Hassan, Soha Abdelaliem Hassan; Khalil, Wael A.; Hassan, Mahmoud A. E.; Yousif, Ahmed I.; Sabry, Omar M.; Wink, Michael; Sobeh, Mansour (Animals, 2021)
This study evaluated the efficacy of Turraea fischeri leaf extract for maintaining the viability of cryopreserved goat sperm. Ejaculated semen was collected from 5 mature Baladi bucks (50-60 kg, 2-4 years of age) and those samples with mass motility ≥ 70% and sperm concentration ≥ 2.5 × 109/mL were selected, pooled, and divided into 4 aliquots. Each aliquot was diluted in Tris-citric-soybean lecithin extender containing a different concentration of T. fischeri leaf extract (0, 125, 250, or 375 µg/mL). Treated semen samples were cooled to 5 °C, transferred to 0.25-mL French straws, and stored in liquid nitrogen (LN2) at −196 °C. After thawing, membrane integrity was examined by transmission electron microscopy, apoptotic activity by Annexin/propidium iodide staining and flow cytometry, and both enzyme activities and antioxidant capacity by spectroscopic assays. The leaf extract at 375 µg/mL significantly improved semen quality as indicated by enhanced total antioxidant capacity, reduced H2O2 concentration, a greater proportion of structurally intact motile sperm, and concomitant reductions in apoptosis and necrosis. The extract also significantly increased the proportion of sperm with a contiguous plasma membrane and intact acrosome (p < 0.05). Furthermore, LC-MS revealed numerous secondary metabolites in the extract that may contribute to sperm cryopreservation.
Gesehen am 04.02.2022